2021
DOI: 10.1186/s12974-021-02235-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and similarities in the neuroimmune response to central administration of poly I:C

Abstract: Background The neuroimmune system is required for normal neural processes, including modulation of cognition, emotion, and adaptive behaviors. Aberrant neuroimmune activation is associated with dysregulation of memory and emotion, though the precise mechanisms at play are complex and highly context dependent. Sex differences in neuroimmune activation and function further complicate our understanding of its roles in cognitive and affective regulation. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…Neuroinflammation is a strong contributor in AD pathophysiology; however, the impact of glial cell sexual dimorphism in the neuroinflammatory response is still yet fairly unknown. Studies characterizing the neuroinflammatory response in male and female C57Bl/6 N mice suggest that type 1 interferons could be one of the potential sex-mediating cytokines that influencing cognition [ 548 ].…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation is a strong contributor in AD pathophysiology; however, the impact of glial cell sexual dimorphism in the neuroinflammatory response is still yet fairly unknown. Studies characterizing the neuroinflammatory response in male and female C57Bl/6 N mice suggest that type 1 interferons could be one of the potential sex-mediating cytokines that influencing cognition [ 548 ].…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
“…Reduced neuronal outgrowth and synaptic density -In vitro: [447][448][449] -Mice: APOE4 knock-in [234] Impaired synaptic plasticity (Long term potentiation) -In vitro: [452] -Mice: APOE knock-in [453] Poor learning and memory -Mice: APOE4 knock-in [456][457][458] Autophagy/Endosomes Decreased/impaired autophagy and mitophagy -In vitro: [470] -Mice: APOE4 knock-in [486] Dysregulated endosomal-lysosomal pathway -Mice: APOE4 knock-in [518] Enlarged endosomes -Humans: [481] -Mice: APOE4 knock-in [518] Reduced mRNA levels of autophagy markers -Humans: [489] Fernández-Calle et al Molecular Neurodegeneration (2022) 17 :62 sexual dimorphism in the neuroinflammatory response is still yet fairly unknown. Studies characterizing the neuroinflammatory response in male and female C57Bl/6 N mice suggest that type 1 interferons could be one of the potential sex-mediating cytokines that influencing cognition [548].…”
Section: Synapsesmentioning
confidence: 99%
“…In a complimentary way to human cohorts, animal models enable strengthening of the causal link between perinatal inflammation and neurodevelopmental impairment [ 119 , 120 , 121 ]. The administration of immunostimulants, such as lipopolysaccharide (LPS) and poly I:C, to pregnant dams has been used to model congenital neurological disorders showing social abnormalities associated with autism spectrum disorder [ 119 , 122 ], cerebral palsy [ 123 , 124 ], white matter injury [ 78 ], and a large array of behavioral abnormalities, according to the gestational age and regimen used [ 125 , 126 ]. Postnatal administration of LPS is also often used to model abnormalities related to neurodevelopment [ 119 , 122 ], with outcomes being dependent on postnatal age, dose and regimen.…”
Section: Early Triggers Of Neurodegeneration In Preterm Infants: Prot...mentioning
confidence: 99%
“…Neuroinflammation is involved in the onset and/or progression of several neurodegenerative and neuropsychiatric disorders (12)(13)(14)(15)(16) and is facilitated by microglia activation and elevated expression of proinflammatory cytokines, including interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) (17)(18)(19)(20). Studies using animal models have shown that systemic and central administration of lipopolysaccharide (LPS) and polyinosinic-polycytidylic acid (poly I:C) can induce neuroinflammation through upregulation of proinflammatory cytokines and glial activation (21)(22)(23)(24)(25)(26)(27). These models can be used for evaluating the anti-inflammatory potential of therapeutics, healthy foods, and nutraceutical products.…”
Section: Introductionmentioning
confidence: 99%